Body - Language - Communication : an international handbook on multimodality in human interaction. - Müller, Cornelia, 1960-; Cienki, Alan J., 1959-; Fricke, Ellen, 1964-; Ladewig, Silva H., 1978-; McNeill, David; Bressem, Jana, 1979- (Handbücher zur Sprach- und Kommunikationswissenschaft,, 2014)
Volume II of the handbook offers the state of the art on how body movements are used for communication around the world. Topics include the functions of body movements, their contexts of occurrence, their forms and meanings, their integration with speech, and how bodily motion can function as language. An interdisciplinary chapter on ‘embodiment’ explores the body and its role in the grounding of language from current theoretical perspectives.